2018
DOI: 10.1371/journal.pone.0199936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal ions on caspase-1 activation and interleukin-1β release in murine bone marrow-derived macrophages

Abstract: Ions released from metal implants have been associated with adverse tissue reactions and are therefore a major concern. Studies with macrophages have shown that cobalt, chromium, and nickel ions can activate the NLRP3 inflammasome, a multiprotein complex responsible for the activation of caspase-1 (a proteolytic enzyme converting pro-interleukin [IL]-1β to mature IL-1β). However, the mechanism(s) of inflammasome activation by metal ions remain largely unknown. The objectives of the present study were to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 69 publications
1
19
0
1
Order By: Relevance
“…In contrast, chromium ions did not cause a significant decrease in cell activity. Investigations by Ferko et al [22] and Kwon et al [16] further support the assumption of cobalt and nickel ions having a stronger impact on monocytes and macrophages in the applied concentrations. Cell death studies by Huk et al [23] proved that chromium ion toxicity needed much higher concentrations than in cobalt stimulation to manifest.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, chromium ions did not cause a significant decrease in cell activity. Investigations by Ferko et al [22] and Kwon et al [16] further support the assumption of cobalt and nickel ions having a stronger impact on monocytes and macrophages in the applied concentrations. Cell death studies by Huk et al [23] proved that chromium ion toxicity needed much higher concentrations than in cobalt stimulation to manifest.…”
Section: Discussionmentioning
confidence: 71%
“…In solution, they form aggregates in the cell culture medium. However, very high concentrations of chromium ions that exceed the investigated range may be able to induce hypoxia in the cell and cause a decrease in viability [22,25]. However, since chromium (VI) ions exhibit up to 1000-fold higher toxicity than chromium(III) ions, our results may not adequately reflect the in vivo effects of chromium [26].…”
Section: Discussionmentioning
confidence: 81%
“…While both Cr and Mo particles activated the NLRP3 inflammasome, no direct conclusions can be made for the inflammasome activating potential of CrMo alloy particles. The proposed stimulatory effects of Co 2+ and other metal ions, as well as cobalt based implant debris also remain speculative [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that such genes may also be involved in the effects of oral exposure of sensitive individuals. Studies with macrophages performed by Ferko and Catelas (2018) have shown that nickel ions can activate the NLRP3 inflammasome, via oxidative stress and NF-jB signalling. This is in line with studies by Li et al (2013) and Li and Zhong (2014), indicating that nickel (II) activates the NLRP3-ASC-caspase-1 immune signalling pathway in antigen-presenting cells, leading to release of the pro-inflammatory cytokine IL-1b.…”
Section: Immunotoxic Activity Of Nickelmentioning
confidence: 99%
“…This implies that such genes may also be involved in the effects of oral exposure of sensitive individuals. Studies with macrophages performed by Ferko and Catelas (2018) have shown that nickel ions can activate the NLRP3 inflammasome, via oxidative stress and NF‐κB signalling. This is in line with studies by Li et al.…”
Section: Assessmentmentioning
confidence: 99%